Comparative investigation on metabolite changes in 'wu mi' production by Vaccinium bracteatum Thunb. leaves based on multivariate data analysis using UPLC–QToF–MS. (15th July 2019) - Fan, Mingcong; Fan, Yihui; Rao, Zhiming; Li, Yan; Qian, Haifeng; Zhang, Hui; Wu, Gangcheng; Qi, Xiguang; Wang, Li
Highlights: Non-targeted metabolic details in VBTL and its juice samples were studied. Metabolic profiling was detected by UPLC–QToF–MS analysis. Some discriminatory metabolites were revealed by multivariate data analysis. Some metabolites were identified as the precursors of iridoid-derived pigment. Abstract: Vaccinium bracteatum Thunb. leaves (VBTL) are used to juicing and dye rice to produce ' Wu mi ', which displays a deep blue color. However, little information is known about the formation mechanism of the pigments. In this research, non-targeted metabolic profiling of VBTL and VBTL juice samples at different growth stages was studied for searching the pigment precursors through UPLC–QToF–MS and multivariate data analysis. The results showed the L * and b * values of ' Wu mi ' produced by spring leaves (stages of 2WAB, 4WAB and 6WAB) were significantly lower than other growth stages. Principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA) of the VBTL and VBTL juice samples showed distinct classifications. Further variable importance in projection (VIP) plot in PLS-DA model demonstrated the discriminatory potential biomarkers between VBTL and VBTL juice samples. Some of the identified biomarkers were tentatively identified as the precursor compounds of the iridoid-derived pigments.